Phenotype and transcriptome analysis reveals chloroplast development and pigment biosynthesis together influenced the leaf color formation in mutants of Anthurium andraeanum ‘Sonate’ - Yang, Yuxia; Chen, Xingxu; Xu, Bin; Li, Yuxia; Ma, Yuehua; Wang, Guangdong (Frontiers in Plant Science, 2015)
Leaf color is one of the well-sought traits in breeding program for Anthurium andraeanum Lind.. Knowledge of mechanisms in anthuriums to produce leaves with different shades of green would help to effectively select desirable traits. In this study, the micro- and ultra-structural and physiological features of leaves on wild type and leaf color mutants (dark green, rubescent, etiolated, albino) in A. andraeanum ‘Sonate’ were analyzed. Results show that chloroplasts of leaf color mutants exhibited abnormal morphology and distribution. Using next generation sequencing technology followed by de novo assembly, leaf transcriptomes comprising of 41,017 unigenes with an average sequence length of 768bp were produced from wild type and rubescent mutant. From the 27,539 (67.1%) unigenes with annotated functions, 858 significantly differently expressed genes (DEGs) were identified, consisting of 446 up-regulated genes and 412 down-regulated genes. Genes that affect chloroplasts development and division, and chlorophyll biosynthesis were included in the down-regulated DEGs. Quantitative real-time PCR (qRT-PCR) analysis validated that the expression level of those genes was significantly lower in the rubescent, etiolated and albino mutant compared to wild type plants, which concurs with the differences in micro- and ultra-structures and physiological features between these two types of plants. Conclusively, the leaf color formation is greatly affected by the activity of chloroplast development and pigment biosynthesis. And the possible formation pathway of leaf color mutant of Anthurium andraeanum ‘Sonate’ is deduced based on our results.